Sports: A Catalyst for Social Progress Peddled by American Athletes - Boudis, Naima; Baghdadi, Assia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
Sport is the most popular cultural practice that is sewn into the social texture and intersects with its driving forces: political, cultural, and economic. The playing field is, by all means, a terrain upon which social struggles and political debacles are reflected. For all intent and purposes, the article capitalizes on the American athletes' role in distorting and reshaping the political dialogue and tilting the balance of power in favor of the oppressed. The article addresses the politics-sport entanglement, be it conflictual or collusive, through a figurational sociology prism to deconstruct the athletes' protests in and off the playing field across the various social figurations.